Influence of semisolid squeeze casting technology on alpha phase and eutectic of AlSi7Mg0.3 - Pastircak, Richard; Martinec, Denis; Kantorikova, Elena (Manufacturing Technology Journal, 2020)
The paper deals with processing of material in semisolid state by the technology of semisolid squeeze casting. The investigated material was a subeutectic aluminium alloy AlSi7Mg0.3. The influence of various preparation meth-ods of batch material on the structure after processing by this technology was studied. Alloy AlSi7Mg0.3 was pre-pared as gravity cast, inoculated, heat treated and by technology of direct squeeze casting. In article is assessed microstructure of castings before and after processing by technology of semisolid squeeze casting. The shape and distribution of eutectic silicon was observed. The shape and the distribution of alpha phase formations has an im-pact on whether micro-volumes of molten eutectic will be closed in alpha phase or will be segregated along the boundaries of alpha phase formations. It was observed the partial inheritance in microstructure. Also the segrega-tion in surface layer was observed.
Keywords: Squeeze Casting; Al-Si Alloys; Semisolid; Crystalization under pressure